Drug repurposing: Fusidic acid as a potential inhibitor of M. tuberculosis FtsZ polymerization – Insight from DFT calculations, molecular docking and molecular dynamics simulations. (March 2020) - Akinpelu, Olayinka I.; Lawal, Monsurat M.; Kumalo, Hezekiel M.; Mhlongo, Ndumiso N.
Abstract: Filamentous Temperature Sensitive Mutant Z (FtsZ), an important cell division protein in bacteria, has been validated as a potential target for antibiotics development. Citric acid has been found to inhibit the polymerization of Mycobacterium tuberculosis (MTB) FtsZ and several other drugs have been predicted as potential inhibitors through a gene ontology-based drug repurposing approach. An in-depth study on four of the predicted drugs; Fusidic acid (FusA), l -tryptophan, Carbamic acid, and 2-(3-guanidinophenyl)-3-mercaptopropanoic acid, as potential inhibitors of MTB-FtsZ polymerization was conducted using Citric acid as reference compound. The applied in silico methods involve DFT calculations, molecular docking and molecular dynamics simulations. DFT approach was applied to evaluate selectivity and stability properties of the predicted drugs. Calculated parameters including non-linear optical properties, charge distribution and electrostatic potential analyses enabled selectivity prediction of these potential drugs. DFT-based descriptors revealed FusA as the most potent compound, even more reactive than the referenced compound, Citric acid, which is also supported from the molecular docking study. Parameters including MM/PBSA binding free energies, RMSD, RMSF, RoG and hydrogen bond analysis also support FusA as the best potential MTB-FtsZ polymerization inhibitor, that forms a stable complex with the protein and impose greatest level of rigidity to the protein. Graphical abstract: In silico study towards identifying potential anti-tuberculosis drugs. Image 1 Highlights: DFT study of the reactivity and selectivity properties of some potential Filamentous Temperature Sensitive Mutant Z (FtsZ) inhibitors was carried out. The obtained DFT-based chemical parameters proved to be significant in evaluating the selectivity, reactivity and stability of the identified drugs. Molecular docking analyses of the selected drugs at the active site of MTB-FtsZ showed high binding affinities and all the drugs (except CA), gave binding energy values higher than the reference citric acid with Fusidic acid having the highest binding affinity as revealed from the binding scores. Molecular dynamics simulations parameters including MM/PBSA binding free energies, RMSD, RMSF, RoG and hydrogen bond analysis also support fusidic acid as the best potential MTB-FtsZ polymerization inhibitor amongst the studied drugs. Fusidic acid forms the most stable complex with the protein and impose the greatest level of rigidity on it. The applied in silico methods could be considered and applied to a wide range of bioactive compounds and enzyme—inhibitor systems.